Athens/Sparta bipolarity in Xenophon’s Hellenika: Helénicas de Jenofonte, Grecia, siglo IV a.C., balance de poder - Bearzot, Cinzia (Araucaria, 2024)
The article traces the reflections found in the Hellenika on the theme of Athens/Sparta bipolarity, with the intention of illustrating Xenophon’s interest in this international arrangement of the Greek world and of emphasizing its repercussions in Xenophon’s historiographical project.